2007
DOI: 10.1080/14622200701416955
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion and cognitive-behavioral treatment for depression in smoking cessation

Abstract: This study is a randomized, double-blind, placebo-controlled clinical trial examining the effects of an intensive cognitive-behavioral mood management treatment (CBTD) and of bupropion, both singularly and in combination, on smoking cessation in adult smokers. As an extension of our previous work, we planned to examine the synergistic effects of CBTD and bupropion on smoking cessation outcomes in general and among smokers with depression vulnerability factors. Participants were 524 smokers (47.5% female, M age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 59 publications
2
72
1
3
Order By: Relevance
“…Consistent with outcomes reported previously ( Brown et al, 2007 ;Wileyto et al, 2004Wileyto et al, , 2005, after including female gender and level of nicotine dependence as covariates ( Table 3 ), smokers receiving bupropion had signifi cantly lower risk of smoking lapse (relative risk [ RR ] = 0.55, 95% CI = 0.42 -0.72, p < .001) and a lower risk of smoking relapse ( RR = 0.48, 95% CI = 0.36 -0.68, p < .001) than smokers receiving placebo. There was no signi fi cant difference in the risk of lapse or relapse across CBT and ST psychosocial treatments.…”
Section: Changes In Positive Affect Negative Affect and Urges To Smsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with outcomes reported previously ( Brown et al, 2007 ;Wileyto et al, 2004Wileyto et al, , 2005, after including female gender and level of nicotine dependence as covariates ( Table 3 ), smokers receiving bupropion had signifi cantly lower risk of smoking lapse (relative risk [ RR ] = 0.55, 95% CI = 0.42 -0.72, p < .001) and a lower risk of smoking relapse ( RR = 0.48, 95% CI = 0.36 -0.68, p < .001) than smokers receiving placebo. There was no signi fi cant difference in the risk of lapse or relapse across CBT and ST psychosocial treatments.…”
Section: Changes In Positive Affect Negative Affect and Urges To Smsupporting
confidence: 82%
“…The present report examined affective trajectories and urges to smoke prior to and on quit day in a sample of 524 smokers participating in a smoking cessation trial studying the individual and combined effects of bupropion versus placebo and CBT versus ST using a 2 脳 2 design ( Brown et al, 2007 ). Previous analyses of quit rates in this sample at the end of 12 weeks of treatment and across 2-, 6-, and 12-month follow-ups indicated that bupropion was signifi cantly more effective than placebo, that CBT did not outperform ST, and that there were no synergistic effects (i.e., no interaction).…”
Section: Original Investigationmentioning
confidence: 99%
“…Using MLM, we quantified the difference in depressive symptoms associated with being abstinent versus smoking at a given assessment. We also were able to test whether history of MDD, which has been associated with greater affective disturbance before and after quitting smoking (Berlin, Spreux-Varoquaux, Said, & Launay, 1997;Brown et al, 2007;Hall et al, 1996;Tsoh et al, 2000), significantly altered the effect of smoking abstinence on depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…El tratamiento cognitivo-conductual con estrategias espec铆ficas para el manejo de los estados de 谩nimo mostr贸 ser beneficioso para la poblaci贸n con depresi贸n recurrente 32,33 , pero fall贸 en mejorar los resultados en poblaci贸n con elevada sintomatolog铆a depresiva 34 . Es necesario pues, seguir investigando con el objetivo de aumentar las tasas de abstinencia en esta poblaci贸n.…”
Section: Discussionunclassified